Collective identities versus social exclusion: The December 2008 Greek youth movement - Psimitis, Michalis (The Greek Review of Social Research, 2011)
This article is trying to highlight some identity aspects of the Greek youth movement that seem to be appropriate in order to understand and interpret similar collective actions of excluded people against social exclusion. The core of the argument is that the notion of "collective identity" is more appropriate than others for our understanding of the complex interactions among different and heterogeneous youth groups that participated actively in the December 2008 riots. In our case, it is precisely the emergence of creative symbolic and physical interactions during rioting, that should be considered as the main factor in the construction of a collective identity that led to the rise of a youth movement in Greece.